MKRN2 knockout causes male infertility through decreasing STAT1, SIX4, and TNC expression - Wang, Lin; Yong, Yan-Ling; Wang, Kun-Kun; Xie, Yun-Xia; Qian, Ying-Chen; Zhou, Feng-Mei; Qiu, Jian-Ge; Jiang, Bing-Hua (Frontiers in Endocrinology, 2023)
Makorin-2 (Mkrn2) is an evolutionarily conserved gene whose biological functions are not fully known. Although recent studies have shed insights on the potential causes of male infertility, its underlining mechanisms still remain to be elucidated. We developed an Mrkn2 knockout mouse model to study this gene, and found that deletion of Mkrn2 in mice led to male infertility. Interestingly, the expression level of STAT1 was significantly decreased in MKRN2 knockout testis and MEF cells. Co-IP assay showed an interaction between MKRN2 and STAT1. Moreover, our results further indicated that MKRN2 regulated the expression level of SIX4 and TNC via the transcription factor EBF2 in mice. These results of our study will provide insights into a new mechanism of male infertility.